Nanotechnology law and policy: An introduction - Karim, M.E. (2013)
Nanotechnology, often referred to as the next industrial revolution after internet, is an interdisciplinary study. It is the science of manipulating technology at atomic scale. One can hardly find any area where the researchers did not attempt to apply it. Based on very optimistic results in many researches around the world, it can easily be inferred that it has virtually limitless potential and it promises epoch making changes in the world. UNESCO traced top ten applications of nanotechnology within the UN Millennium Development Goals (MDGs)- (a) Energy storage, productions and conversion, (b) Agricultural productivity enhancement, (c) Water treatment and remediation, (d) Disease diagnosis and screening, (e) Drug delivery systems, (f) Food processing and storage, (g) Air pollution and remediation, (h) Construction, (i) Health monitoring, (j) Vector and pest detection and control. However, to many persons and organisations, nanotechnology is the next asbestos and are reluctant to welcome it with open mind. This is a matter of great concern that the world community is still in search of a consensus on legal and regulatory frameworks to govern it. As of now, there are at least six areas i.e. product safety, privacy and civil liberties, occupational health and safety (OH&S), intellectual property (IP), international law and environmental law, which are directly related with nanotechnology research and application and law must intervene in these areas. While the benefits that can be achieved by using nanomaterials are whole-heartedly welcomed and appreciated, this paper aims at introducing the legal aspects of nanotechnology. The mistakes which hindered the introductions of genetically modified food or nuclear energy should not be repeated and the application of nanotechnology should be encouraged within approved legal framework.